Essential Oils from Plant Extracts and Theirs Application as Antimicrobial Agents in Food Products - Rattanapitigorn, Panida (Journal of Food Technology, Siam University, 2018)
Essential oils are natural aroma compounds from plants, herbs, and spices, with biological activity as antimicrobial agents and have been exploited as natural preservatives in food products. There are many reports which highlighted the efficiency of essential oils against food spoilage, food pathogen, and molds. The latter is considered as the pathogen responsible for postharvest decay of agricultural products and causes severe economic losses. The usage limit of essential oils in food products is caused by rapidly evaporating and strong flavor of essential oils. The above-mentioned limitation of essential oils are pleading for the application of methods and technology in order to improve the efficiency of essential oils and have led to an interest in the use of essential oils as potential alternative natural antimicrobial agents in food products for ensuring food safety as the consumer concerns.